Changes in governance to achieve forest development - Naidu, M. Kamal (2004)
Forests have a history of being a vital support resource for life in its all forms. Piecemeal approaches have been made to manage this resource for sustenance and development of society. An effort has been made in this article to trace the history of forest administration and development, changes in the approach towards forest administration after Independence and the road map for forest management in the 21st Century. It emphasises the need for paradigm shift in the forest management objectives through societal participation. The new development objectives have also to ensure environmental conservation and welfare of neighbourhood community. - Reproduced.
Keywords: Good governance; Forest management